State Building and National Identity Reconstruction in the Horn of Africa
XV, 246 p. 4 illus., 1 illus. in color.
Keywords: This book examines post-secession and post-transition state building in Somaliland, Somalia, South Sudan and Sudan. It explores two intimately linked, yet analytically distinct themes: state building and national identity reconstruction following secession and collapse. In Somaliland and South Sudan, rearranging the state requires a complete metamorphosis of state institutions so that they respond to the needs and interests of the people. In Sudan and Somalia, the reconfiguration of the remains of the state must address a new reality and demands on the ground. All four cases examined, although highly variable, involve conflict. Conflict defines the scope, depth and momentum of the state building and state reconstruction process. It also determines the contours and parameters of the projects to reconstitute national identity and rebuild a nation. Addressing the contested identity formation and its direct relation to state building would therefore go a long way in mitigating conflicts and state crisis.